Preclinical Metabolism, Pharmacokinetics and In Vivo Analysis of New Blood-Brain-Barrier Penetrant Fingolimod Analogues: FTY720-C2 and FTY720-Mitoxy - Enoru, Julius O.; Yang, Barbara; Krishnamachari, Sesha; Villanueva, Ernesto; DeMaio, William; Watanyar, Adiba; Chinnasamy, Ramesh; Arterburn, Jeffrey B.; Perez, Ruth G. (PLOS ONE, 2016)
Parkinson’s disease (PD) is a neurodegenerative aging disorder in which postmortem PD brain exhibits neuroinflammation, as well as synucleinopathy-associated protein phosphatase 2A (PP2A) enzymatic activity loss. Based on our translational research, we began evaluating the PD-repurposing-potential of an anti-inflammatory, neuroprotective, and PP2A stimulatory oral drug that is FDA-approved for multiple sclerosis, FTY720 (fingolimod, Gilenya®). We also designed two new FTY720 analogues, FTY720-C2 and FTY720-Mitoxy, with modifications that affect drug potency and mitochondrial localization, respectively. Herein, we describe the metabolic stability and metabolic profiling of FTY720-C2 and FTY720-Mitoxy in liver microsomes and hepatocytes. Using mouse, rat, dog, monkey, and human liver microsomes the intrinsic clearance of FTY720-C2 was 22.5, 79.5, 6.0, 20.2 and 18.3 μL/min/mg; and for FTY720-Mitoxy was 1.8, 7.8, 1.4, 135.0 and 17.5 μL/min/mg, respectively. In hepatocytes, both FTY720-C2 and FTY720-Mitoxy were metabolized from the octyl side chain, generating a series of carboxylic acids similar to the parent FTY720, but without phosphorylated metabolites. To assess absorption and distribution, we gave equivalent single intravenous (IV) or oral doses of FTY720-C2 or FTY720-Mitoxy to C57BL/6 mice, with two mice per time point evaluated. After IV delivery, both FTY720-C2 and FTY720-Mitoxy were rapidly detected in plasma and brain; and reached peak concentrations at the first sampling time points. After oral dosing, FTY720-C2 was present in plasma and brain, although FTY720-Mitoxy was not orally bioavailable. Brain-to-plasma ratio of both compounds increased time-dependently, suggesting a preferential partitioning to the brain. PP2A activity in mouse adrenal gland increased 2-fold after FTY720-C2 or FTY720-Mitoxy, as compared to untreated controls. In summary, FTY720-C2 and FTY720-Mitoxy both (i) crossed the blood-brain-barrier; (ii) produced metabolites similar to FTY720, except without phosphorylated species that cause S1P1-mediated-immunosuppression; and (iii) stimulated in vivo PP2A activity, all of which encourage additional preclinical assessment.